High five-year mortality rates of ischemic stroke subtypes: A prospective cohort study in Brazil. Issue 5 (July 2019) - Cabral, Norberto Luiz; Nagel, Vivian; Conforto, Adriana B; Magalhaes, Pedro SC; Venancio, Vanessa G; Safanelli, Juliana; Ibiapina, Felipe; Mazin, Suleimy; França, Paulo; Liberato, Rafaela M; Longo, Alexandre; Zetola, Viviane F
Background: Studies regarding long-term outcomes of ischemic stroke subtypes are scarce in low- and middle-income countries. We aimed to measure the five-year prognosis of ischemic stroke subtypes in Joinville, Brazil. Methods: All first-ever ischemic strokes that occurred in Joinville in 2010 were followed-up for five years. Results: We included 334 ischemic stroke patients. Over five years, 156 died, 51 had a recurrent stroke, and 128 were free of recurrent stroke. The overall cumulative risk of death was 17% (95% CI, 13% to 22%) at 30 days and 47% (95% CI, 41% to 52%) after five years. Undetermined with incomplete investigation ischemic stroke had a significantly worse survival probability (β −4.91; 95% CI, −6.31 to −3.50; p  < 0.001), followed by cardioembolic ischemic stroke (β −3.07; 95% CI, −4.32 to −1.83; p  < 0.001) and large artery disease ischemic stroke (β −1.95; 95% CI, −3.30 to −0.60; p  = 0.005). The survival probability of undetermined with negative investigation or cryptogenic ischemic stroke did not differ significantly from small artery disease ischemic stroke (β −1.022; 95% CI, −3.37 to −1.43; p  = 0.414). The five-year mortality for small artery disease ischemic stroke was 30% (95% CI, 22% to 39%) and 47% (95% CI, 35% to 60%) for large artery ischemic stroke. The risk of stroke recurrence was 2% in the first year and 5% in the second year. The proportion of disability among survivors in the first month ranged from 8% (95% CI, 3–15) for small artery disease ischemic stroke to 40% (95% CI, 30–52) for cardioembolic ischemic stroke patients. Conclusions: Cardioembolic and undetermined with incomplete investigation ischemic stroke sub-types have a poor long-term prognosis. An alarming finding was that our patients with both small and large artery ischemic stroke had higher five-year mortality rates compared with subjects from high-income countries.